Factor Identification of Categorical Type Related to the Structural Condition of Bogota’s Sewage Pipelines Stemming from Concepts of the Information’s Entropy - Hernández Rodríguez, Natalie; Obregón Neira, Nelson; Torres, Andrés (Ingeniería Solidaria, 2016)
Introduction: this article is the result of the research project “Factor identification of categorical type related to the structural condition of Bogota’s sewage pipelines stemming from concepts of information’s entropy” financed by the Mastery in Hydro-systems of the Pontifical University Javeriana and developed in 2014 and 2015. The objective was to identify the influence of factors of qualitative type (grid type, material of the associated road surface and material of the pipeline) on the structural grade obtained from CCTV  inspections in Bogota during 2007 and 2011.Methodology: the entropy’s concept of mutual information was studied to differentiate the following categorical variables: type of pipelines, type of road surface over the pipeline and materials of the pipeline.Results: obtained from the application of concepts like entropy and mutual information show that the structural classification is independent from the type of pipeline, since they present elevated values of joined entropy and imply a high degree of uncertainty in their relation.Conclusions: the categorical variables studied are important factors to account in an impairment model of sewage pipelines; they also provide decision-making to direct the inspection plans of sewage in the city.